Am I Going to be Okay? Weathering the storms of mental illness, addiction, and grief - Whittam, Debra (Henderson, Nevada Turning Point International, 2016)
This is a thought provoking true life story of growing up in a family riddled with mental illness and addiction and the effect it had on the children during their formative years. It touches profoundly on the relationship between family fears and frustrations and how they affect a person's level of self-esteem. The author, Debra Whittam, a licensed, practicing mental health therapist casts an unashamed light on her shame-based childhood and subsequent decent into her own sea of addiction, loneliness and denial as well as the steps she took for recovery and wellness. This is a story that will be helpful to all who might need to throw off fear and frustration and gain the courage and self-confidence to produce positive changes in their lives. --Publisher.
Keywords: Memoir -- psyhology; Women-psychology -- Psychology - applied